YouTube in the secondary classroom: how teachers use instructional videos in mainstream classrooms. Issue 2 (15th March 2022) - Fyfield, Matthew
ABSTRACT: Online streaming has transformed instructional videos into a seemingly ubiquitous part of learning and teaching in secondary schools. Much of the research into video use in secondary education has either proposed best practices or focused on a-typical pedagogies like flipped learning and distance education. The use of videos in mainstream schooling is under-examined. Drawing on the experiences of nine Australian secondary teachers this research examines ways in which instructional videos, mostly from YouTube, were used in mainstream classrooms. These uses included replacing the teacher as direct instructor, displaying historical footage, and the demonstration of abstract phenomena. However, some practices were less predictable, such as a virtual duplication of teachers or the use of controversial videos to prompt critical discussion. A connection emerged between teacher experience and the innovative use of instructional videos, suggesting that the use of videos is a pedagogical skill that improves with wisdom of practice.